The Effect of Using Quizizz Application on Students™ Vocabulary Mastery of VIII Grade Class at SMP Negeri 1 Delitua - Mahrina, Yuliza; Harahap, Yulia Sari (Universitas Negeri Medan, 2024)
Mastery of vocabulary needs to be done to improve students™ ability to communicate, therefore it is very important for students to master vocabulary so that they can communicate with someone. Many Indonesian students have difficulty mastering vocabulary in English, especially students of SMP Negeri 1 Delitua, including students who lack vocabulary and have difficulty remembering unfamiliar vocabulary. The objective of the research was found the effect of using Quizizz application on students™ vocabulary mastery of VIII Grades Class at SMP Negeri 1 Deli Tua. The method of this research was quantitative research. The research sample consisted of 30 students in class VIII-1 as the experimental class and 30 students in class VIII-2 as the control class. From the data that has been analyzed, the researcher found that the experimental pre-test results which were initially 67,40 had an increase in the experimental post-test of 85,67 whereas in the pre-control there was also an increase, but not too significant. The output the significant value (Sig) based on the mean is 0.112 > 0.05. On the output results above, the sig (2-tailed) value is 0.000 < 0.05. Therefore, it can be concluded that the variance of the post-test data for the experimental class and the post-test data for the control class are the same or homogeneous. This can work effectively and efficiently in achieving students™ vocabulary at SMP Negeri 1 Delitua and this learning has been successfully implemented and can achieve students' vocabulary mastering.